Development of bevacizumab in advanced cervical cancer: pharmacodynamic modeling, survival impact and toxicology. (March 2015) - Eskander, Ramez N; Tewari, Krishnansu S
ABSTRACT : Historically, patients with metastatic, persistent or recurrent cervical cancer had limited therapeutic options. Despite several Phase II/III clinical trials, the combination of cisplatin and paclitaxel remained the most effective chemotherapeutic regimen. In 2014, publication of Gynecologic Oncology Group 240 represented the emergence of an alternate and effective therapeutic option. This prospective, randomized, Phase III clinical trial explored the impact of adding the antiangiogenic agent bevacizumab to two separate cytotoxic chemotherapy backbones. Importantly, the study met its primary end point, showing a survival advantage of approximately 4 months without detriment in quality of life. As such, a review of bevacizumab and its application in patients with advanced-stage cervical cancer is warranted.